Free-living marine nematodes of the genus Richtersia Steiner, 1916 (Desmodorida: Richtersiidae) from the Sea of Japan - Revkova, Tatiana N.; Sergeeva, Nelli G. (Zootaxa, 2024)
Two new species Richtersia japonica sp. nov. and Richtersia amurica sp. nov. are described from the shallow water of the Sea of Japan. Both new species are characterized by the presence of multispiral amphidial fovea 3.5 turns in males and one turn in females; two unequal spicules and gubernaculum with anterior apophyses. R. japonica sp. nov. is most similar to R. beibuwanensis Fu, Cai, Boucher, Cao & Wu, 2013 and R. staresensis Soetaert & Vincx, 1987 in having arrangement of longitudinal rows of spines and presence of anterior apophyses on gubernaculum, but differs from them by the length of the spicules and in de Man a value in males. R. amurica sp. nov. is most similar to R. coomansi Soetaert & Vincx, 1987 and R. inaequalis Riemann, 1966 in having arrangement of longitudinal spine rows beginning at the level of the amphidial fovea and in long hairy spines on the tail of females. But it differs from them by presence of anterior apophyses on gubernaculum and length of the spicules. Data on the geographic and bathymetric distribution of all valid Richtersia species are provided.